2013
DOI: 10.1089/cyber.2012.0255
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Turkish Adolescent's Internet Use: Possible Predictors of Internet Addiction

Abstract: The purpose of this study is to investigate the internet use of Turkish adolescents, with a (particular) focus on the risk of Internet addiction. A web-based questionnaire was completed by a total of 4,311 adolescents attending public high schools in grades 9-12, in a small-sized city in western Turkey. Ages ranged from 15 to 19 years, 54 percent were female and 46 percent male. The questionnaire included items on sociodemographic information, Internet usage, and a Turkish version of the Young's Internet Addic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
54
3
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 24 publications
11
54
3
8
Order By: Relevance
“…A total of seven studies used the IAT for Internet addiction assessment in adolescents and children aged 8 to 24 years [61][62][63][64][65][66][67], with sample sizes ranging from 1,618 [65] to 17,599 participants [63]. Although the same measurement instrument has been used in these studies, various cut-offs have been applied to demarcate addiction or excessive use across studies.…”
Section: Prevalence Of Internet Addiction In Adolescentsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of seven studies used the IAT for Internet addiction assessment in adolescents and children aged 8 to 24 years [61][62][63][64][65][66][67], with sample sizes ranging from 1,618 [65] to 17,599 participants [63]. Although the same measurement instrument has been used in these studies, various cut-offs have been applied to demarcate addiction or excessive use across studies.…”
Section: Prevalence Of Internet Addiction In Adolescentsmentioning
confidence: 99%
“…In addition to the prevalence estimates reported, the studies have found that in adolescents, Internet addiction is associated with the following sociodemographic variables: higher family income levels [61,63], male gender [45, 61-63, 65, 66, 81, 83], female gender [48], being left behind (i.e., abandoned), and migrant [68], living in rural areas [81], being in senior high school, and having a monthly spending over 100 RMB [45]. The discrepancy between findings concerning associations between Internet addiction and gender can possibly be explained by the measures utilised, i.e., Liu et al [48] found that a higher percentage of girls reports excessive usage behaviours, which might be indicative of their increased problem awareness relative to boys.…”
Section: Sociodemographic Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Por um lado, o sexo feminino procura socializar mais através do uso dos websites de redes sociais online, salas de chat, enquanto o sexo masculino tem preferência por atividades relacionadas com jogos multi-users online e jogos single-user (Ak, Koruklu, & Yılmaz, 2013;Durkee et al, 2012), e consulta de jornais e revistas (Ak et al, 2013).…”
Section: Introductionunclassified
“…Entretanto, longe de haver consenso, o termo "internet addiction" (dependên-cia de internet) é mais comumente utilizado na literatura sobre esse tema e, sendo assim, foi adotado no presente estudo (Ak, Koruklu, & Yılmaz, 2013;Lam, Peng, Mai, & Jing, 2009;Park et al, 2008;Yen, Yen, Chen, Chen, & Ko, 2007).…”
unclassified